Implications of COVID-19 on women workers in the service sector. A special focus on Spain - Toffanin, Tania; Galarza-Fernández, Emelina; Martagón Vázquez, Virginia; Rivas-Flores, José Ignacio (Transform! Europe network for alternative thinking and political dialogue, 2022)
The spread of the SARS-CoV-2 virus and its devastating effects has brought to light the contradictions already present in our society. These include the gender gap and the low value placed on care work. In this contribution, we focus on observing the effects of the syndemic in the Spanish service sector. In the future, it is our intention to collaborate in research aimed at investigating the other two issues, which have not been ad- dressed in this contribution. In southern Europe, Spain, like Italy, was one of the countries which was worst affected by the SARS-CoV-2 virus. Italy and Spain share a labour market structure marked by strong gender segregation, high precariousness of women’s employment, and wage restraint in the most female-dominated sectors. The following study highlights the issue that employment does not always enable women to escape from hardship and poverty. Moreover, the increase in female employment in itself says little about the conditions women face in the labour market. The crisis produced by the spread of the SARS-CoV-2 virus has put a spotlight on the structural na- ture of gender discrimination in society and the presence of working conditions, which, according to ILO indicators, are far from satisfactory.
Informe aportación española a proyecto europeo.
Keywords: COVID-19 - Influencia y consecuencias; Mercado de trabajo; Trabajadoras; Mujeres - Trabajo - Investigación; Discriminación en el trabajo; Mujeres trabajadoras